If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9007 + -5667 = x Combine like terms: 9007 + -5667 = 3340 3340 = x Solving 3340 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3340 + -1x = x + -1x Combine like terms: x + -1x = 0 3340 + -1x = 0 Add '-3340' to each side of the equation. 3340 + -3340 + -1x = 0 + -3340 Combine like terms: 3340 + -3340 = 0 0 + -1x = 0 + -3340 -1x = 0 + -3340 Combine like terms: 0 + -3340 = -3340 -1x = -3340 Divide each side by '-1'. x = 3340 Simplifying x = 3340
| -2y-1(3y-9)=7+9(-3-y) | | X+7x+4=172 | | -3x=-32x+151 | | x^2-mx=32 | | 1x+5(-5)=-23 | | 7x+0=4 | | 7x+0=4 | | 7-m=m+4 | | 4x(4-5)= | | 3=23-f | | 8=b-5 | | 8(-4x+16)= | | 9s+9=-45 | | 2.3=p-0.6 | | 8(-4+16)= | | 8x+80=344 | | -7.95+X=14.95 | | 42=31-7(5-4w) | | K+(-8)=11 | | Log(6)(3x+8)=4 | | 82.5-2.25+2x=338.5 | | 2x+8=sqrt(x+4) | | 9z+15-2z= | | 2(0.5x+7)-3(2.5x+8)= | | -8x=5x-9 | | 9x^3+60x^2-21x=0 | | 2n+(2n+1.2)=4n+(2n+0.2) | | 9x^2+10x-2=0 | | (p-2)(p+4)+(p-2)(p+6)=0 | | 3/4c+3=12 | | 1+u=(-6) | | 2n+(2n+1.2)=4n+(2n+0.1) |